HIV-1 Infection and Glucose Metabolism Reprogramming of T Cells: Another Approach Toward Functional Cure and Reservoir Eradication - Kang, Shuang; Tang, Hong (Frontiers in Immunology, 2020)
With the emerging of highly active antiretroviral therapy, HIV-1 infection has transferred from a fatal threat to a chronic disease that could be managed. Nevertheless, inextricable systemic immune activation and chronic inflammation despite viral suppression render patients still at higher risk of HIV-1 associated non-AIDS complications. Immunometablism has nowadays raised more and more attention for that targeting metabolism may become a promising approach to modulate immune system and play a role in treating cancer, HIV-1 infection and autoimmune diseases. HIV-1 mainly infects CD4+ T cells and accumulating evidence has brought to light the association between T cell metabolism reprogramming and HIV-1 pathogenesis. Here, we will focus on the interplay of glycometabolism reprogramming of T cells and HIV-1 infection, making an effort to delineate the possibility of utilizing immunometabolism as a new target towards HIV-1 management and even sterilizing cure through eliminating viral reservoir.